Effects of silty sand and pH on the formation of corrosion film and corrosion behaviour of low-Cr steel in the CO2 environment. (4th July 2022) - Zhao, Yonggang; Liu, Wei; Chen, Longjun; Yang, Weijian; Fan, Yueming; Zhang, Tianyi; Dong, Baojun; Sun, Zongteng
ABSTRACT: The effects of silty sand and pH on the corrosion characteristics of 1Cr steel were investigated. The results revealed that silty sand changed the nucleation behaviour of FeCO3 crystal from homogeneous nucleation to heterogeneous nucleation through increasing the critical supersaturation of FeCO3 . The compactness and protection of corrosion film were improved by silty sand. The amorphous FeCO3 content decreased as the pH increased in the CO2 environment with silty sand, while the Cr(OH)3 content increased. The critical pH for the good corrosion resistance of 1Cr steel was 4.5. The amorphous FeCO3 dominated the protective properties of corrosion film when the pH was lower than the critical pH, whereas the Cr(OH)3 was predominant when the pH was higher than the critical pH. Therefore, the corrosion resistance of 1Cr steel was reduced and then enhanced with increasing pH under silty sand condition.